COVID-19 and its Linguistic Variants from “Miss Rona” to “Boomer Remover” - Tatiana Canziani (European Scientific Journal, ESJ, 2022)
The COVID-19 pandemic has had an enormous impact on everyday language and has led to unprecedented linguistic innovation and lexical explosion, ranging from the medicalisation of everyday language to the creation of new word formations that have defined new situations and overcome the fear of an unknown disease. In this paper, after briefly introducing the main linguistic features of English neologisms created to define changes in life style during the pandemic, a survey of the main English monikers coined to rename COVID-19 will be given taking into account the most recent studies on the subject.